Antimicrobial Resistance Profiles of Escherichia coli from Diarrheic Weaned Piglets after the Ban on Antibiotic Growth Promoters in Feed - Do Kyung-Hyo; Byun Jae-Won; Lee Wan-Kyu (MDPI AG, 2020)
This study aimed to survey the antimicrobial resistance profiles of 690 pathogenic Escherichia coli isolates obtained from Korean pigs with symptoms of enteric colibacillosis between 2007 and 2017, while assessing the change in antimicrobial resistance profiles before and after the ban on antibiotic growth promoters (AGPs). Following the Clinical and Laboratory Standards Institute guidelines, the antimicrobial resistance phenotype was analyzed through the disk diffusion method, and the genotype was analyzed by the polymerase chain reaction. After the ban on AGPs, resistance to gentamicin (from 68.8% to 39.0%), neomycin (from 84.9% to 57.8%), ciprofloxacin (from 49.5% to 39.6%), norfloxacin (from 46.8% to 37.3%), and amoxicillin/clavulanic acid (from 40.8% to 23.5%) decreased compared to before the ban. However, resistance to cephalothin (from 51.4% to 66.5%), cefepime (from 0.0% to 2.4%), and colistin (from 7.3% to 11.0%) had increased. We confirmed a high percentage of multidrug resistance before (95.0%) and after (96.6%) the ban on AGPs. The AmpC gene was the most prevalent from 2007 to 2017 (60.0%), followed by the blaTEM gene (55.5%). The blaTEM was prevalent before (2007-2011, 69.3%) and after (2012-2017, 49.2%) the ban on AGPs. These results provide data that can be used for the prevention and treatment of enteric colibacillosis.